Viability of Bali bull epididymal spermatozoa preserved at 3–5oC in Tris extender with different lactose concentrations - Muhammad Rizal (Jurnal Ilmu Ternak dan Veteriner, 2009)
Cauda epididymal spermatozoa could be used as an alternative source of gamete in the application of various reproductive technologies, because the spermatozoa is motile and has ability for fertilizing the oocyte. The objective of this research was to examine the effectivity of lactose in maintaining viability of Bali bull epididymal spermatozoa preserved at 3–5oC. Five testis with epididymides of Bali bulls were obtained from slaughterhouse. Epididymal spermatozoa was collected by the combination of slicing, flushing and tissues pressure of cauda epididymides with physiological saline (0.9% NaCl). Collected-spermatozoa was divided in equal volume into three tubes and diluted with Tris extender containing 20% egg yolk (control), Tris extender + 0.3 g lactose/100 ml (L0.3), and Tris extender + 0.6 g lactose/100 ml (L0.6), respectively. Diluted-spermatozoa was stored in refrigerator at 3–5oC. Quality of diluted-spermatozoa including percentages of motile spermatozoa (MS), live spermatozoa (LS), and intact plasma membrane (IPM) were evaluated every day during storage at 3–5oC for six days. Data were analyzed using completely randomized design with three treatments and five replications. Results of this study showed that mean spermatozoa concentration, percentage of MS, percentage of LS, percentage of abnormal spermatozoa, percentage of cytoplasmic droplet, and percentage of IPM of Bali bull fresh epididymal spermatozoa were 11,222.5 million cell/ml, 75, 86.75, 10.5, 14, and 86.75%, respectively. At day-7 storage, percentages of MS, LS, and IPM for L0.3 (39, 50.6, and 51.6%) and L0.6 (39, 51.4, and 51.8%) were significantly (P<0.05) higher than control (29, 41.8, and 42.4%). In conclusion, addition of lactose in Tris extender extended viability of Bali bull epididymal spermatozoa preserved at 3–5oC. Key Words: Lactose, Preservation, Epididymal Spermatozoa, Bali Bull